Impact of body mass index on long-term outcomes in Japanese patients following percutaneous coronary intervention: The Juntendo PCI Registry. Issue 3 (September 2018) - Endo, Hirohisa; Dohi, Tomotaka; Shitara, Jun; Wada, Hideki; Doi, Shinichiro; Naito, Ryo; Konishi, Hirokazu; Tsuboi, Shuta; Ogita, Manabu; Kasai, Takatoshi; Okazaki, Shinya; Isoda, Kikuo; et al.
Highlights: The association between body mass index and adverse cardiac events was examined. Underweight patients had a higher mortality than normal and overweight patients. The rate of extremely obese patients is low in Asia. It is one of the main reasons that the typical "obesity paradox" was not observed. Abstract: Background: The prognostic long-term impact of body mass index (BMI) on East Asian patients with coronary artery disease remains unclear. Methods: An observational retrospective cohort study was carried out involving 3571 patients who had undergone percutaneous coronary intervention (PCI) from 2000 to 2013. Patients were divided into the following five groups according to baseline BMI: Group 1 (underweight 1, BMI ≤20.0 kg/m 2 ); Group 2 (underweight 2, BMI = 20.1–22.5 kg/m 2 ); Group 3 (normal weight, BMI = 22.6–25.0 kg/m 2 ); Group 4 (overweight 1, BMI = 25.1–27.5 kg/m 2 ); and Group 5 (overweight 2, BMI ≥27.6 kg/m 2 ). We then evaluated the association between BMI and both all-cause and cardiac death after PCI. Results: The ratio of patients in the five groups was as follows: Group 1, 9.2%; Group 2, 21.6%; Group 3, 34.1%; Group 4, 21.1%; and Group 5, 14.5%. A decrease in age was observed from underweight to overweight, as was an increased prevalence of hypertension, diabetes mellitus, dyslipidemia, and smoking. The median follow-up period was 6.3 years (interquartile range, 3.2–9.6 years). In total, 473 deaths (frequency, 13.2%) were identified, including 183 (5.1%) cardiac deaths during follow-up. In unadjusted Cox proportional hazard analysis, using normal weight as the reference, underweight, but not overweight, was associated with a greater risk of both all-cause and cardiac death. In an adjusted model, Group 1 had the highest risk for all-cause death (hazard ratio, 1.58; 95% confidence interval, 1.19–2.10; p  = 0.0019); however, no significant differences were found for the risk of all-cause and cardiac death between normal weight and overweight patients. Conclusion: The results of the present long-term follow-up study do not support the so-called "obesity paradox, " but rather, suggest that underweight Japanese patients are at greater risk for all-cause mortality following PCI.